COMPARATIVE EFFECTIVENESS AND SAFETY OF VEDOLIZUMAB AND ANTI-TUMOR NECROSIS FACTOR AGENTS IN OLDER ADULTS WITH INFLAMMATORY BOWEL DISEASES IN MEDICARE ADMINISTRATIVE CLAIMS DATABASE. (21st January 2021) - Kochar, Bharati; Pate, Virginia; Kappelman, Michael; Long, Millie; Ananthakrishnan, Ashwin; Chan, Andrew; Sandler, Robert
Abstract: Background: The number of older adults with inflammatory bowel diseases (IBD) is increasing. Older adults with IBD are less likely to receive effective immunosuppression. We aimed to determine efficacy and safety of biologic therapies in older adults with IBD. Methods: We conducted a retrospective cohort study using an active comparator, new user design in a 20% random sample from the 50 state Medicare claims database between May 2014 and December 2018. We included patients who initiated vedolizumab or an anti-tumor necrosis factor (TNF)-α agent (infliximab, adalimumab, golimumab or certolizumab) following 12-months of continuous enrollment in Medicare fee-for-service Parts A/B/D without either study drug. Patients were required to be ≥65 years old and have ≥2 international classification of disease (ICD) codes of Crohn's disease (CD) or ulcerative colitis (UC). We excluded patients who received other biologic therapies and/or those who had ≥2 codes for other immunologic conditions. Pertinent co-variates included were age, sex, race Charlson Co-morbidity Index (CCI), predicted probability of frailty, healthcare utilization and baseline IBD medications. The outcomes of interest were hospitalizations, IBD-related surgery and new corticosteroid use ≥ 60 days after drug initiation. We described the study population, assessed health care utilization and use of other IBD medications. We estimated crude incidence rates and hazard ratios (HR) adjusted for the covariates using standardized mortality ratio (SMR) weights. Results: We identified 488 vedolizumab users and 2, 213 anti-TNF users. The median age was 72 years in the vedolizumab cohort and 71 years in the anti-TNF cohort; 12% of both cohorts were aged ≥80 years. Differences in the two cohorts existed with regards to sex, race, baseline healthcare utilization and IBD-related medications, but all the baseline differences were balanced by weighting measured by a standardized mean difference (SMD) <0.1 (Table 1). After weighting, vedolizumab users were less likely to be hospitalized in the 12 months after biologic initiation (HR: 0.81, 95% CI: 0.68 – 0.96). While there was no significant difference in IBD related hospitalizations, older adults with IBD were less likely to have an infection-related hospitalization (HR: 0.39, 95% CI: 0.23 – 0.65). There were no significant differences in IBD related surgery and steroid use after induction (Table 2). Conclusions: In this large, retrospective cohort study of older IBD patients who were new users of vedolizumab and anti-TNF agents, we found that older patients initiated on vedolizumab were significantly less likely to have an infection-related hospitalization. However, there were no significant differences in IBD-related hospitalizations, IBD-related surgery or corticosteroid use after biologic induction.